Persepsi Cantik di Kalangan Karyawan Milenial (Analisis AISAS atas Pengaruh Terpaan Iklan Kecantikan di Kalangan Karyawati Pabrik Cikarang Selatan Kabupaten Bekasi Jawa Barat) - Yunani, Asni Sri; Hidayat, Mochamad Taufiq (Marcommers : Jurnal Marketing Communication and Advertising, 2023)
The concept of beauty always changes from time to time. One of the main factor determine is the rapid development of the advertising media industry, which led to the perception of beauty in society. This study aims to describe advertisment element exposure of Wardah “Feel the beauty” version and perceptions of beauty among millennial employees and explain the effect of Wardah advertisement elements exposure that formed the perceptions of beauty among factory employees in South Cikarang, Bekasi, West Java.This research uses AISAS theoretical framework that shows Attata, Attention, Interest, and the desire to search (Search), to decide (Action) and finally encourage customers to share (Share). The concept develop by tow theories with indicators of Frekuensi, duration, visual and audio and perception theory involving sensation, attention, expectations, motivation and memory.This study use positvism paradigm with quantitative approach and causal explanatory research design. The data collected by survey conducted for millennial employees who working in the factory area in South Cikarang District Bekasi West Java. About 381 respondent involved as sample of this research that defined using cluster sampling in the industrial area, i.e.: BIIE Hyundai, Delta Silicon, EJIP, and Jababeka II.